A credibility-driven evaluation of a community-based perinatal substance use disorder collaborative care model - Jäderholm, Christina M.; Williams, Teshanee T.; Wipfli, Brad M.; Messer, Lynne C.; Winett, Liana B. (Frontiers in Public Health, 2025)
IntroductionEffectively treating substance use disorder (SUD) during pregnancy is critical to preventing adverse health outcomes for both parents and children, including overdose death and family separation. Although evidence supports investing in parental recovery through comprehensive care and support, these approaches remain under-examined, with community perspectives often marginalized due to evaluation challenges. This study evaluated the Substance Use Network (SUN) program, a community-based perinatal SUD recovery model in North Carolina.MethodsWe used a patient-focused journey mapping approach to assess participant engagement, health outcomes, and alignment between participant and provider experiences. The evaluation used a mixed-methods approach, incorporating participant medical record review (n = 29), surveys (n = 29), focus groups (n = 7), and staff interviews (n = 11). Quantitative data assessed engagement metrics, treatment adherence, and birth outcomes. Thematic analysis of qualitative data from focus groups and survey responses provided insights into participants’ experiences with the program. Finally, interviews provided program staff perspectives.FindingsParticipants were predominantly White non-Hispanic, all reported opioid use, most had polysubstance use, and 94% of participants maintained adherence to treatment. At the time of delivery, 87% of infants were born at term. Notably, 100% of infants born to parents enrolled in the first trimester were delivered at term. Through qualitative data, we identified areas of alignment and conflict between participants’ needs and organizational policies. Motivated by concerns for their baby’s health, participants emphasized opioid agonist treatment and non-judgmental, sustained support as key to recovery. Staff explained the importance of robust treatment and social service coordination, while recognizing a need for more training and sustainable funding.ConclusionThe journey map provides a comprehensive evaluation framework that enhances credibility and represents community perspectives meaningfully. This approach, which captures lived experiences alongside clinical outcomes, offers a replicable model for evaluating and strengthening community-based recovery programs. These insights can inform future improvements in perinatal SUD treatment and public health strategies to support pregnant and parenting individuals in recovery.